Pembiasaan Harian Kurangi Sampah Plastik (KURSAMTIK) untuk Menumbuhkan Karakter Cinta Lingkungan pada Siswa SDN Banjaranyar 04 Brebes, Jawa Tengah - Leni Yunitasari; Dhiniaty Gularso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue of plastic waste remains a major concern in elementary education as it affects both environmental cleanliness and the development of students’ environmental awareness. This article aims to describe the implementation of the KURSAMTIK (Reduce Plastic Waste) program as a daily habituation activity to foster environmental care and responsibility among students at SD N Banjaranyar 04 Brebes, Central Java, Indonesia. This study employed a descriptive qualitative approach through observation, interviews, and documentation. Data were collected from teachers, students, and school curriculum documents. The results show that KURSAMTIK has been integrated into the daily program of the Merdeka Curriculum and supports three key dimensions of the Graduate Competency Profile (Profil Capaian Lulusan – PCL): independence, physical and mental health, and collaboration. Students demonstrated significant behavioral changes: 92% began bringing personal lunch containers, and plastic waste volume decreased by 66% within three months. The program effectively cultivates responsibility, independence, and environmental awareness. Therefore, KURSAMTIK can be considered a best practice for environmental character education in elementary schools.